Respostas

2013-03-15T16:15:18-03:00

Resolvendo preimeiro os parenteses:

 {42+[(45-19)-(18-3)+1]-(28-15)-1}=

 {42+[(26)-(15)+1]-(13)-1}=

 {42+[(26-15)+1]-13-1}=

 {42+[(11)+1]-14}=

 {42+[12]-14}=

 {42-2}=

Portanto:

 {42+[(45-19)-(18-3)+1]-(28-15)-1}= 40

2 3 2
2013-03-15T16:23:58-03:00

{42+[(45-19)-(18-3)+1]-(28-15)}-1 = 
{42+[26-15+1]-13-1} =
{42+12-13-1} =
  {54-13-1} = 
     {41 - 1} =

         40 = 

                                                                        40 "
 

1 5 1